The OT-II model reveals dual in vitro and in vivo immunomodulatory properties of CD6 in T cell activation - Leyton-Pereira, Alejandra; Fernández-Delgado, Irene; Rodríguez-Lagunas, María José; Català, Cristina; Casadó-Llombart, Sergi; Martin-Cofreces, Noa Beatriz; Bustos-Morán, Eugenio; Díaz-Garrido, Natalia; Consuegra-Fernández, Marta; Calpena, Ana Cristina; Aranda, Fernando; Velasco-de Andrés, María; et al. (Frontiers in Immunology, 2025)
IntroductionCD6 is a signal transducing transmembrane glycoprotein expressed on T-cells and a subset of B and NK cells that has emerged as a promising therapeutic target in autoimmunity and cancer.The extracellular domain of CD6 interacts with endogenous (CD166/ALCAM, Galectins 1 and 3,CD318/CDCP-1 and CD44) and exogenous (Pathogen-associated Molecular Patterns) ligands, and the phosphorylatable Thr/Ser/Tyr residues of its intracellular region can dock signal transduction effectors.This, together with its physical association with the T cell receptor (TCR) complex at the immunological synapse (IS) supports a relevant immunomodulatory role for CD6 in T cell activation , differentiation and survival. However, activation or inhibitory signalling properties have been observed by CD6 contingent on different experimental settings,rendering its precise function not well understood.MethodsTo ascertain CD6’s immunomodulatory role, we investigated the effects of CD6-deficiency in vitro and in vivo under physiological antigen-specific stimulation in TCR transgenic OT-IImice.ResultsIn vitro ovalbumin (OVA)-specific stimulation of Cd6-/- OT-II splenocytes and in vivo OVA-induced delayed-type hypersensitivity (DTH) supported a negative modulatory role of CD6 in lymphocyte activation. On the contrary, IS studies in Cd6-/- OT-II T cells and OVA-loaded dendritic cells advocate for a positive modulatory role.DiscussionThese findings support CD6 as a “dual” immunomodulatory receptor capable of either amplify or attenuate T-cell activation in different experimental contexts. This dual role should be taken into consideration while translating experimental data in to clinical applications, particularly in the development of CD6-targeted therapies for autoimmune disorders and cancer.